Checklist for the preparation and review of pain clinical trial publications: a pain-specific supplement to CONSORT. (May 2019) - Gewandter, Jennifer S.; Eisenach, James C.; Gross, Robert A.; Jensen, Mark P.; Keefe, Francis J.; Lee, David A.; Turk, Dennis C.
Abstract: Introduction: Randomized clinical trials (RCTs) are considered the gold standard when assessing the efficacy of interventions because randomization of treatment assignment minimizes bias in treatment effect estimates. However, if RCTs are not performed with methodological rigor, many opportunities for bias in treatment effect estimates remain. Clear and transparent reporting of RCTs is essential to allow the reader to consider the opportunities for bias when critically evaluating the results. To promote such transparent reporting, the Consolidated Standards of Reporting Trials (CONSORT) group has published a series of recommendations starting in 1996. However, a decade after the publication of the first CONSORT guidelines, systematic reviews of clinical trials in the pain field identified a number of common deficiencies in reporting (eg, failure to identify primary outcome measures and analyses, indicate clearly the numbers of participants who completed the trial and were included in the analyses, or report harms adequately). Objectives: To provide a reporting checklist specific to pain clinical trials that can be used in conjunction with the CONSORT guidelines to optimize RCT reporting. Methods: Qualitative review of a diverse set of published recommendations and systematic reviews that addressed the reporting of clinical trials, including those related to all therapeutic indications (eg, CONSORT) and those specific to pain clinical trials. Results: A checklist designed to supplement the content covered in the CONSORT checklist with added details relating to challenges specific to pain trials or found to be poorly reported in recent pain trials was developed. Conclusion: Authors and reviewers of analgesic RCTs should consult the CONSORT guidelines and this checklist to ensure that the issues most pertinent to pain RCTs are reported with transparency. Abstract : Use of this checklist by authors and reviewers will improve quality and transparency in reporting randomized clinical trials of pain treatments.